How community sport programs may improve the health of vulnerable population groups: a program theory - Karen Van der Veken; Emelien Lauwerier; Sara J. Willems (BMC, 2020)
Abstract Background Groups at risk of exclusion from society appear to have a lower health status and more health-related problems. Prevention efforts in these groups are not always successful, and new ways have to be sought by which health messages can be delivered. Many agree on low-threshold sport activities, also called 'community sports', to be a powerful tool to target socially vulnerable groups. Until now, it has not been investigated how and when such sport initiatives may be able to impact health outcomes in socially vulnerable populations. This study aims at developing a program theory that clarifies the mechanisms and necessary conditions for sport programs to be effective in health promotion. Such a program theory may constitute a backbone for developing health promotion initiatives within a sport for development setting. Methods We developed a program theory using a realist research design. We build on an extensive data set consisting of the insights of key stakeholders and participants of various community sport organizations at the one hand, and on relevant theoretical frameworks at the other hand. Data were collected through participatory observations of soccer trainings and related group activities, interviews with key stakeholders and participants, document analysis and two focus groups with stakeholders from associated social partnership organizations. Results The health promoting effect of community sport on socially vulnerable groups seems not to result from an improved physical condition or sport-technical skills as such, but from processes of experiential learning among peers, incremental responsibility-taking and reflexivity. On the condition that participants feel safe, are stimulated to reflect and enabled to become actor of themselves and their situation, these processes are likely to lead to increased self-esteem, self-efficacy and motivation to set and pursue personal (health) goals. The key-influencing factor in these processes is the coach, who therefore needs to be adequately skilled in, for example, social vulnerability, motivational coaching and group dynamics. Conclusions The program theory developed in this study offers insights in the mechanisms proper to, and necessary conditions for community sport to be a lever for health promotion in socially vulnerable groups. Motivational processes at individual level and group connectivity are at the basis of personal health goal-setting. One of the necessary conditions is that these processes are guided by community sport coaches skilled in the meaning and impact of social exclusion, and capable of connecting with the target group.